Clinical Evaluation of an Investigational 5 mL Wearable Injector in Healthy Human Subjects - Wendy D. Woodley; Wen Yue; Didier R. Morel; Audrey Lainesse; Ronald J. Pettis; Natasha G. Bolick (Wiley, 2021)
An investigational wearable injector (WI), the BD Libertas Wearable Injector (BD Libertas is a trademark of Becton, Dickinson and Company), was evaluated in an early feasibility clinical study for functional performance, tissue effects, subject tolerability, and acceptability of 5 mL, non‐Newtonian ~ 8 cP subcutaneous placebo injections in 52 healthy adult subjects of 2 age groups (18-64 years and ≥ 65 years). Randomized WI subcutaneous injections (n = 208, 4/subject) were delivered to the right and left abdomen and thigh of each subject, 50% (1 thigh and 1 abdomen) with a defined movement sequence during injection. Injector functional performance was documented. Deposition was qualified and quantified with ultrasound. Tissue effects and tolerability (pain) were monitored through 24 hours with corresponding acceptability questionnaires administered through 72 hours. WI (n = 205) automatically inserted the needle, delivered 5 mL ± 5% in 5.42 minutes (SD 0.74) and retracted. Depots were entirely (93.2%) or predominantly (5.4%) localized within the target subcutaneous tissue. Slight to moderate wheals (63.9%) and erythema (75.1%) were observed with ≥ 50% resolution within 30-60 minutes. Subject pain (100 mm Visual Analog Scale) peaked mid‐injection (mean 9.1 mm, SD 13.4) and rapidly resolved within 30 minutes (mean 0.4 mm, SD 2.6). Subjects' peak pain (≥ 90.2%), injection site appearance (≥ 92.2%) and injector wear, size, and removal (≥ 92.1%) were acceptable (Likert responses) with 100% likely to use the injector if prescribed. Injection site preference was divided between none (46%), abdomen (25%), or thigh (26.9%). The investigational WI successfully delivered 5 mL viscous subcutaneous injections. Tissue effects and pain were transient, well‐tolerated and acceptable. Neither injection site, movement or subject age affected injector functional performance or subject pain and acceptability.